Consumer purchasing behavior towards honey in Malaysia - Ee, Pey Wen (2016)
Honey already exists in the world millennia years ago. It is commonly used in daily lifestyle such as drink and energy booster at that time. Apart from that, it is also treated as traditional and natural supplement. In ancient time, humans already started to use it as traditional medicine. Nowadays, medical technology has advanced by leaps and bounds and thus becoming a standard globally. People trusts in the advance medical technology instead of the traditional medicine such as honey. However, there are certain of peoples who still believed on the health benefit provided by honey. Moreover, the world population of human living in this world is around 7 billion which still increasing year by year. The production of honey is still far from enough to fulfil the human’s needs and wants. In addition, humans thought is varies from each other, therefore humans has different perceptive toward the health benefit provided by honey. Thus, the main purpose of this study is to determine the factors influence the consumer purchasing behaviour towards honey in Malaysia. A survey was conducted among 1018 respondents from each states of Malaysia. In this study, theory of reasoned action model has been adapted in order to have a better and clear understanding towards the consumer purchasing behaviour. Besides that, the data analyses were conducted by descriptive analysis, reliability analysis, factor analysis and multiple regression analysis. The factors that extracted from the factors analysis are health benefit, brands, colour, price, and taste. Based on the multiple regression analysis, the correlation has shown relationship between the factors and the consumer purchasing intention is low correlation but the F ratio is highly significant. Therefore, it has indicated that the honey purchaser is suitable in the model.